From Ethnobotany to Food Innovation: Applications and Functional Potential of Mashua (Tropaeolum tuberosum). - Vera, W. (2025)
Mashua (Tropaeolum tuberosum), a resilient and underutilized Andean tuber, is a highpotential nutritional and functional food innovation resource. This review surveys information on the nutritional composition, bioactive profile, and functional properties of the tuber based on a comprehensive literature search conducted in the Scopus database. The search strategy employed eight Boolean operators combining the following terms: (“Tropaeolum tuberosum” OR “mashua”) AND (“bioactive compounds” OR “functional properties” OR “glucosinolates” OR “antioxidant activity” OR “food processing”). The review included English-language research articles published between 2000 and 2025. Its diverse constituents, such as glucosinolates, phenolics, and anthocyanins, have antioxidant, anti-inflammatory, and antimicrobial activities. Technologies such as freeze-drying, microencapsulation, and 3D printing make it easier to preserve these bioactive components and ensure their use in novel food products. Although Mashua has potential, its widespread adoption remains limited by its distinct sensory characteristics and the lack of clinical validation regarding its effect on human health. To extract the full potential of mashua as a functional ingredient for the global food industry, consensus evidence exists around the need for standardized analytical methodologies, technological innovation, and sustainable value chain development.